On Approaches to Assessing Contribution of Russian Universities in the Implementation of National Projects - I. V. Arzhanova; M. V. Shiryaev; S. N. Mityakov (Высшее образование в России)
The article provides a brief review of the literature related to the analysis of approachesto assessing the effectiveness of the universities of the country. The authors propose to consider the universities as key performers of strategic decisions at various hierarchical levels. Each of the strategic planning documents includes indicator systems and their target values in dynamics over the years. Monitoring of these indicators allows us to determine the effectiveness of the implementation of the strategic planning documents as a whole. The methodology given in the article for assessing effectiveness of the universities is directly or indirectly related to target indicators laid down in the strategic planning documents. This enables to evaluate the contribution of the universities to the development of socio-economic systems at various levels: industries, regions and the country as a whole. As an example, the approach to the development of the system of indicators is considered, which makes it possible to evaluate the contribution of the universities to the implementation of national projects. In the initial (pilot) version the system included 30 indicators directly related to national projects “Education”, “Science”, “Digital Economics” and a number of others. The article presents the results of testing of the developed methodology and the system of indicators at a number of the flagship universities of the Volga Federal District.